Correlations of the liquefaction resistance of sands in spreader dumps of lignite opencast mines with CPT tip resistance and shear wave velocity. Issue 124 (September 2019) - Wichtmann, T.; Kimmig, I.; Steller, K.; Triantafyllidis, T.; Back, M.; Dahmen, D.
Abstract: Correlations between the liquefaction resistance of sands in spreader dumps of lignite opencast mines on one side and the CPT tip resistance or the shear wave velocity on the other side have been developed based on an extensive experimental study on 10 different sands. The cyclic resistance ratio C R R ( N f = 10 ) for a failure in 10 cycles, defined as the liquefaction resistance herein, was determined from undrained cyclic triaxial tests for all materials. The CPT tip resistance q c was measured in soundings performed in a calibration chamber. The shear wave velocity v S was obtained from measurements in a triaxial cell by means of bender elements. All three quantities C R R ( N f = 10 ), q c and v S were determined for different relative densities D r . In case of q c and v S also the pressure-dependence was examined in order to derive suitable equations for a pressure-normalization being necessary for the interpretation of field test data, giving values q c 1 and v S 1 for a mean effective stress of p '  = 100 kPa. The procedure for the development of the C R R ( N f = 10 ) - q c 1 and C R R ( N f = 10 ) - v S 1 correlations based on the experimental data is explained. The correlations derived for the various sands in the present study are analyzed with respect to the influence of the grain size distribution curve and compared to respective relationships for natural soils or uncompacted recent artificial fills from the literature. Highlights: CPT tip resistance qc of sands from dumps was measured in a calibration chamber Shear wave velocity vS was measured with bender elements Liquefaction resistance CRR was obtained from undrained cyclic triaxial tests CRR-qc correlations for sands from dumps run atter than those from literature CRR-qc and CRR-vS correlations for dumps depend on grain size distribution curve